Dietary ecological traits of extinct mammalian herbivores from the last glacial termination at the Pilauco Site, Chile. (September 2022) - González-Guarda, Erwin; Tornero, Carlos; Petermann-Pichincura, Alia; Ramírez-Pedraza, Iván; Pino, Mario; Corti, Paulo; Cortés, Leslie; Osorio, Felipe; Barrientos, Úrzula; Espinoza, Angelo; Agustí, Jordi
Abstract: Stable isotopes are a powerful tool for reconstructing the past. However, environmental factors not previously considered can lead to misinterpretations. Our study presents a novel analysis of the feeding behavior of the megafauna that inhabited the Pilauco ecosystem in south-central Chile during the last glacial termination. We analyzed a suite of modern plant and animal samples from closed-canopy forests to establish an isotopic baseline with which to compare stable isotope results from fossil megafauna. Using the modern samples as a reference, the δ 13 C results from the Pilauco megafauna indicate feeding behaviors in forested areas. These results were then calibrated with dental calculus samples and coprolites, which suggest the coexistence of graze- and grass-dominated mixed-feeder diets. The δ 15 N values found in Pilauco megafauna are not consistent with modern reference data sets or with the low δ 15 N values of extinct proboscideans from other contemporaneous and nearby sites. Probably, the δ 15 N values of the Pilauco ecosystem were not primarily affected by climate, but rather by disturbance factors (e.g., grazing effect). Our results indicate that the Pilauco megafauna fed mainly on arboreal vegetation; however, non-isotopic proxies indicate that they were also eating open vegetation (e.g., herbs and grasses).